Induction of estrus and hormonal profile in buffalo treated with norgestomet ear implant - PATEL, D M; SARVAIYA, N P; PATEL, A V; PARMAR, A P; DUGWEKAR, Y G (The Indian Journal of Animal Reproduction, 2003)
A group of uniform healthy buffalo (n=10) and buffalo heifers (n=10) were induced to estrus andsynchronized during breeding and non-breeding seasons, using Norgestomet ear implant (Crestar,Intervet). All the buffaloes and 70% heifers exhibited estrus, which attributed to 90 and 80% responseduring breeding and non-breeding season respectively. Seasonal condition and reproductive statusof buffaloes are reflected in their respective endocrine profiles. After insertion of implant and injectionof estradiol velerate, circulating estradiol levels showed marked elevation and also remained higherduring estrus. All the experimental buffaloes subsequently became cyclic.
Keywords: Anestrus; Buffalo; Induction of estrus; Norgestomet ear implant; Progesterone